2017
DOI: 10.1021/acs.jced.7b00023
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagrams and Physicochemical Properties for the Ternary System (CsCl + NaCl + H2O) at T = (298.15, 308.15, and 318.15) K

Abstract: Complete phase diagrams and physico-chemical properties for the ternary system (CsCl + NaCl + H 2 O) were determined at T = (298.15, 308.15, and 318.15) K, respectively. The X-ray diffraction method and Schreinemaker's wet residue method were used to verify the solid phase. The phase diagrams show this ternary system is a complex type. Three crystallization regions were found corresponding to the single salt NaCl, a compound CsCl•2NaCl•2H 2 O, and a solid solution series [Cs 1−x (Na•H 2 O) x ]Cl (x in [Cs 1−x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In order to evaluate the reliability of the experimental data in this work, the solubility data, densities, and refractive indices of the subternary systems at 298.15 K were compared with the results in the literature. 11,18,19 It was found that the experimental results agreed well with the reported data, indicating our experimental and analytical methods were reliable. 2− −H 2 O) system are fundamental for the quaternary system, which are listed in Table 2, and the composition of the liquid phase of the system are listed in Table 4.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…In order to evaluate the reliability of the experimental data in this work, the solubility data, densities, and refractive indices of the subternary systems at 298.15 K were compared with the results in the literature. 11,18,19 It was found that the experimental results agreed well with the reported data, indicating our experimental and analytical methods were reliable. 2− −H 2 O) system are fundamental for the quaternary system, which are listed in Table 2, and the composition of the liquid phase of the system are listed in Table 4.…”
Section: Resultssupporting
confidence: 74%
“…The concentration of Cl – was analyzed by the titration method. The mass fraction of Cs + and SO 4 2– were analyzed by the gravimetric analysis through the precipitation of CsB­(C 6 H 5 ) 4 and BaSO 4 , respectively. , Therein, the uncertainties for the analytical results for Cl – , Cs + , and SO 4 2– are ±0.003, ±0.05, and ±0.0005 (in mass fraction), respectively. Moreover, the concentration of Na + was calculated according to the ion balance of ions and verified by inductively coupled plasma–optical emission spectrometry (Prodigy, Leeman Corp. America).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hitherto, a series of aqueous solution systems concerning the element lithium or cesium have been investigated, such as the ternary system Li 2 SO 4 + MgSO 4 + H 2 O at 323.15 and 373.15 K; Cs 2 SO 4 + Li 2 SO 4 + H 2 O at 298 K , and 308 K; NaCl + CsCl + H 2 O at 298.15, 308.15, and 318.15 K; Rb + (Cs + ), Mg 2+ //SO 4 2– + H 2 O at 298.2 K; CsCl 2 + MgCl 2 + H 2 O at 298.15 K; CsCl + KCl + H 2 O and CsBr + KBr + H 2 O at 298.2 K; Na + , Rb + (Cs + )//SO 4 2– + H 2 O at 298.2 K; Cs 2 CO 3 + Rb 2 CO 3 + H 2 O 2 + H 2 O; the quaternary systems Cs 2 SO 4 + CsCl + Rb 2 SO 4 + RbCl + H 2 O and Cs 2 SO 4 + CsCl + K 2 SO 4 + KCl + H 2 O at 298.2 K; Li + , Na + , Cs + //SO 4 2– + H 2 O at 298.2 K; KCl + RbCl + CsCl + H 2 O at 298.15 K; , Li + , K + , Mg 2+ //SO 4 2– + H 2 O at 273.15 K; LiCl + Li 2 SO 4 + Li 2 B 4 O 7 + H 2 O at 273 K; and LiCl + MgCl 2 + Li 2 SO 4 + MgSO 4 + H 2 O at 323.15 K …”
Section: Introductionmentioning
confidence: 99%